2021
DOI: 10.1126/sciimmunol.abf0558
|View full text |Cite
|
Sign up to set email alerts
|

A tumor-specific mechanism of T reg enrichment mediated by the integrin αvβ8

Abstract: Regulatory T cells (Tregs) that promote tumor immune evasion are enriched in certain tumors and correlate with poor prognosis. However, mechanisms for Treg enrichment remain incompletely understood. We described a mechanism for Treg enrichment in mouse and human tumors mediated by the αvβ8 integrin. Tumor cell αvβ8 bound to latent transforming growth factor–β (L–TGF-β) presented on the surface of T cells, resulting in TGF-β activation and immunosuppressive Treg differentiation in vitro. In vivo, tumor cell αvβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…According to the literature, ITGB8 is the integrin β8 subunit and it can form integrin αvβ8 with integrin αv subunit [27] . Recent studies have shown that tumor cell αvβ8 expression was associated with immunosuppressive Treg gene expression, Treg enrichment, and increased tumor growth [34] . Integrin αvβ8 could bind to latent TGF-β (L-TGF-β) and activate TGF-β without releasing it [35] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, ITGB8 is the integrin β8 subunit and it can form integrin αvβ8 with integrin αv subunit [27] . Recent studies have shown that tumor cell αvβ8 expression was associated with immunosuppressive Treg gene expression, Treg enrichment, and increased tumor growth [34] . Integrin αvβ8 could bind to latent TGF-β (L-TGF-β) and activate TGF-β without releasing it [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells continually present self and non-self- antigens, thereby promote tolerance via control of Tregs. Integrin αvβ8 on dendritic cells can activate TGF-β, a process that can contribute to the development of pTregs, especially in tumours ( Seed et al, 2021 ). Disruption of dendritic cell-expressed TGFβ receptor (TGFβR) impairs the tolerogenic function of dendritic cells and fosters autoimmunity ( Ramalingam et al, 2012 ).…”
Section: Functional Characteristics Of Human Regulatory T Cellsmentioning
confidence: 99%
“…However, not all T lymphocytes mediate defense functions, a proportion of them, especially the regulatory T cells mediate tolerogenic functions that are required during the whole course of pregnancy and other developmental and regenerative processes ( Weirather et al, 2014 ; Boothby et al, 2020 ; Fung et al, 2020 ; Green et al, 2021 ). As important as these regulatory T cell functions are, regulatory T cells also promote tumor growth and have been identified as promising targets in anti-tumor therapies ( Paluskievicz et al, 2019 ; Bai et al, 2020 ; Seed et al, 2021 ).…”
Section: Assays For the Assessment Of Immunomodulatory Pnd Activitiesmentioning
confidence: 99%